Determinants Factors of The Implementation of Health Protocols to Prevention of Covid-19 - Indra Martias; Luh Pitriyanti (JURNAL PROTEKSI KESEHATAN, 2022)
Abstract The risk of mobility and community gathering in the workplace has a large potential for COVID-19 transmission. This study aims to determine the determinant factors related to the application of health protocols to prevent the spread of Covid-19. This study is an analytical study with a cross-sectional design to determine the relationship between knowledge, attitudes, gender, education, and management policies with the implementation of health protocols in the workplace. The minimum number of samples is 100. The sampling technique was carried out with the snowball technique using an online questionnaire. The results showed that there was a significant relationship between education and the implementation of health protocols (p = 0.004; OR = 4,842) and management policies with the implementation of protocols (p = 0.012; OR = 4,176). It is hoped that factors related to the implementation of health protocols will continue to be improved and improved. Keywords : Covid-19, determinant factor, workplace Abstrak Risiko mobilitas dan berkumpulnya masyarakat di tempat kerja memiliki potensi penularan COVID-19 yang besar. Penelitian ini bertujuan untuk mengetahui faktor determinan yang berhubungan dengan penerapan protokol kesehatan untuk mencegah penyebaran COVID-19 di tempat kerja. Penelitian ini adalah penelitian yang bersifat analitik dengan desain cross sectional untuk mengetahui hubungan pengetahuan, sikap, jenis kelamin, pendidikan dan kebijakan manajemen dengan penerapan protokol kesehatan di tempat kerja. Jumlah minimal sampel adalah 100 sampel. Teknik pengambilan sampel dilakukan dengan purposive sampling menggunakan kuesioner online. Hasil penelitian menunjukkan terdapat hubungan yang signifikan antara pendidikan dengan penerapan protokol kesehatan (p = 0.004; OR = 4,842) dan kebijakan manajemen dengan penerapan protokol (p = 0,012 ; OR = 4,176). Diharapkan faktor yang berhubungan dengan penerapan protokol kesehatan terus diperbaiki dan ditingkatkan. Kata Kunci : COVID-19, faktor determinan, tempat kerja